PENINGKATAN KUANTITAS DAN KUALITAS BATIK, ECOPRINT JOMBANG DENGAN INOVASI TEKNOLOGI MESIN DRYROOM INFRARED.: Peningkatan Kuantitas Dan Kualitas Batik, Ecoprint Jombang Dengan Inovasi Teknologi Mesin Dryroom Infrared. - Zuraidah, Safrin; Ichlas Wahid,; Ilya Farida,; Roosida Ully T, Liosten Rianna (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2025)
Abstract Oemah Batik Nusantria, a batik business in Jombang, faces serious challenges due to the low quality of its products, particularly batik and eco-print, compared to its competitors. The main problem stems from the high humidity in Wonosalam, which slows down the fabric drying process by 1–3 days. This condition reduces color quality, especially in natural eco-prints, and hinders productivity. Additionally, designs that are unappealing to younger generations and a limited number of artisans further restrict production capacity.The Community Empowerment Partnership Program (PKM) aims to improve the competitiveness of partners by offering innovative solutions. The technological innovation implemented is an infrared dryroom machine, which has succeeded in accelerating the drying process of 12 pieces of fabric to 90 minutes (300% efficiency), while increasing productivity by up to 60% and maintaining color quality. To address design issues, the PKM team provided training in motif innovation using economical cardboard canting caps, resulting in five modern motifs that appeal to various groups. Training in natural and synthetic dyeing was also provided to improve quality and production capacity by up to 40%. This synergy demonstrates the role of academics in providing technological solutions that combine local wisdom to support the sustainability of the batik business in Sumberjo village. Keywords: batik , eco-print, infrared, dryroom